Innovative therapies for invasive fungal infections in preclinical and clinical development. (1st September 2020) - Yu, Yidong; Albrecht, Krystyna; Groll, Jürgen; Beilhack, Andreas
ABSTRACT: Introduction: The incidence of life-threatening invasive fungal infections (IFIs) has increased significantly in recent years. Current therapeutic options for IFIs are limited. Only four major classes of antifungal agents are available to clinicians, namely polyenes, azoles, echinocandins, and flucytosine. These antifungals have particular drawbacks, including toxicity, drug-drug interactions, and increasing antifungal resistance. Consequently, there is an urgent need for new antifungals to combat IFIs. Areas covered: This review illuminates new classes of synthetic antifungal drugs under preclinical and clinical investigations that have novel mechanisms of action; it also examines innovative strategies for the in vivo delivery of antifungal drugs. Expert opinion: It is imperative to expand the pipeline of antifungals to tackle emerging fungal resistance against conventional antimycotic drugs, toxicity, and drug-drug interactions. This unmet medical need should not be underappreciated.